Uptake of severe acute respiratory syndrome coronavirus 2 spike protein mediated by angiotensin converting enzyme 2 and ganglioside in human cerebrovascular cells - McQuaid, Conor; Solorzano, Alexander; Dickerson, Ian; Deane, Rashid (Frontiers in Neuroscience, 2023)
Abstract Introduction: There is clinical evidence of neurological manifestations in coronavirus disease-19 (COVID-19). However, it is unclear whether differences in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)/spike protein (SP) uptake by cells of the cerebrovasculature contribute to significant viral uptake to cause these symptoms. Methods: Since the initial step in viral invasion is binding/uptake, we used fluorescently labelled wild type and mutant SARS-CoV-2/SP to study this process. Three cerebrovascular cell types were used (endothelial cells, pericytes and vascular smooth muscle cells), in vitro. Results: There was differential SARS-CoV-2/SP uptake by these cell types. Endothelial cells had the least uptake, which may limit SARS-CoV-2 uptake into brain from blood. Uptake was time and concentration dependent, and mediated by angiotensin converting enzyme 2 receptor (ACE2), and ganglioside (mono-sialotetrahexasylganglioside, GM1) that is predominantly expressed in the central nervous system and the cerebrovasculature. SARS-CoV-2/SPs with mutation sites, N501Y, E484K and D614G, as seen in variants of interest, were also differentially taken up by these cell types. There was greater uptake compared to that of the wild type SARS-CoV-2/SP, but neutralization with anti-ACE2 or anti-GM1 antibodies was less effective. Conclusion: The data suggested that in addition to ACRE2, gangliosides are also an important entry point of SARS-CoV-2/SP into these cells. Since SARS-CoV-2/SP binding/uptake is the initial step in the viral penetration into cells, a longer exposure and higher titer are required for significant uptake in normal brain. Gangliosides, including GM1, could be an additional potential SARS-CoV-2 and therapeutic target at the cerebrovasculature.